Body weight predicts Nicotinamide N-Methyltransferase activity in mouse fat. (2nd January 2018) - Rudolphi, Bianca; Zapp, Benedikt; Kraus, Nils A.; Ehebauer, Franziska; Kraus, Bettina J.; Kraus, Daniel
ABSTRACT: Aim : Nicotinamide N-methyltransferase (NNMT) is a novel regulator of energy homeostasis in adipose tissue. NNMT expression is higher in obese mice than in lean mice, and NNMT knockdown prevents diet-induced obesity. Little is known about the regulation of enzyme activity during the development of obesity. The aim of this study was to analyze NNMT activity in tissues of mice with incipient and established obesity.Methods : A fluorescence-based, sensitive, low-volume, high-throughput method was developed to assay NNMT activity. C57BL/6 mice were fed a high-fat diet for 4 weeks (incipient obesity) and for 12 weeks (established obesity). Tissues and serum were harvested and analyzed.Results : NNMT activity was highest in subcutaneous white fat (55.0 µU/mg), followed by epididymal white fat (35.6 µU/mg), brown adipose tissue (7.8 µU/mg), liver (7.6 µU/mg), and lung (7.3 µU/mg). Little activity was detected in heart, skeletal muscle, and kidney. No activity was found in serum samples. Body weight predicted NNMT activity in white fat, but not in brown fat or any other tissue, and only in incipient obesity. With established obesity, this association was lost.Conclusions : As obesity develops, body weight predicts NNMT activity in white adipose tissue, but not in any other tissue, consistent with a specific role of adipose-tissue NNMT in the regulation of body weight.